EVALUATING THE EFFECTIVENESS OF WORK OF SCHOOL FOR THE HYPERTENSIVE PATIENT AT THE LEVEL OF PRIMARY HEALTH CARE (American Journal of Interdisciplinary Research and Development, 2024)
The past 5-year data from 222 randomiy selected outpatient cards of hypertensive patients who were followed up at a family polyclinic (n=54) and in a number of rural ambulances (n=168) of the Republik of Uzbekistan were retrospectively analyzed. The physicians from the Tashkent family polyclinic and rural ambulances of a number of the Republic’s regions, who had taken 10-month retraining courses for general practitioners, were questioned. Two handred and fhifty-six hypertensive patients followed up at the family hospital and rural ambulances were interviewed using questionnaires and examined. Then some of them (a study group) took a course of training at a school for the hypertensive patient and the others (a comparison group) did not parcitipate in the education program. All the patients were followed up for 2 years with a subsequent reexamination and study. Most outpatient cards give recommendations for non-drug treatment incompletely. In a number of cases, the physicians who attach importance to the detection and correction of risk factors has substantially increased after education. The patients who had taken training courses were found to be significantly (р